2014
DOI: 10.1098/rsbl.2014.0408
|View full text |Cite
|
Sign up to set email alerts
|

Size matters: plasticity in metabolic scaling shows body-size may modulate responses to climate change

Abstract: Variability in metabolic scaling in animals, the relationship between metabolic rate ( R ) and body mass ( M ), has been a source of debate and controversy for decades. R is proportional to M b , the precise value of b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 21 publications
3
35
3
Order By: Relevance
“…For example, a study of the catfish Silurus meridionalis showed that body size and temperature do not have independent effects on metabolic rate, as assumed by the MTE, but rather have significant interactive effects [73]. This study supported extensive past and recent work showing that the metabolic scaling slope in ectothermic organisms often varies with ambient temperature ( [19,20,54,56,57,59,[72][73][74][75][76]; also see Section 3.4), which has been ignored by proponents of the MTE. Therefore, multivariate models incorporating the effects of body size and temperature on metabolic rate should include an interactive term (e.g., [73,74]).…”
Section: Multivariate Effects Of Body Size and Temperature (And Othersupporting
confidence: 69%
See 1 more Smart Citation
“…For example, a study of the catfish Silurus meridionalis showed that body size and temperature do not have independent effects on metabolic rate, as assumed by the MTE, but rather have significant interactive effects [73]. This study supported extensive past and recent work showing that the metabolic scaling slope in ectothermic organisms often varies with ambient temperature ( [19,20,54,56,57,59,[72][73][74][75][76]; also see Section 3.4), which has been ignored by proponents of the MTE. Therefore, multivariate models incorporating the effects of body size and temperature on metabolic rate should include an interactive term (e.g., [73,74]).…”
Section: Multivariate Effects Of Body Size and Temperature (And Othersupporting
confidence: 69%
“…Inverse relationships occur between scaling slopes and elevations, even when one calculates the latter as the mass-specific metabolic rate at the midpoint of a scaling relationship, a measure not mathematically linked to the slope, thus removing the autocorrelation effect [54][55][56][57]. Moreover, the elevations of scaling relationships (and by association the slopes) often relate to various intrinsic and extrinsic factors affecting metabolic level (e.g., lifestyle, activity level, and temperature [54][55][56][57][58][59][60][61]). According to the MLBH, at high levels of resting metabolism, the scaling slope should be chiefly influenced by surface-area-related resource uptake and (or) metabolic waste (including heat) loss (thus approaching 2/3, assuming isomorphic body shapes).…”
Section: Relationships Between Metabolic Scaling Slopes and Elevationsmentioning
confidence: 99%
“…Therefore, in sedentery (immobile) organisms, a thermally increased metabolic level should result in a lowered metabolic scaling exponent, whereas, in actively mobile animals, a thermally increased metabolic level may result in a variety of effects on the metabolic scaling exponent, depending on the relative size-specific effects of T a on activity level (also see [26]). Consistent with this hypothesis, sedentery or mostly stationary organisms (including plants, oysters, mussels, chitons, and ascideans) usually show strong negative associations between T a and the resting metabolic scaling exponent (e.g., [110][111][112][113][114]), whereas actively mobile animals show a variety of responses (as reviewed in [16,26]; and as shown in an unpublished data set). As further evidence, when the effects of activity are removed in an actively mobile species, such as the fish Coregonus albula, T a and the resting metabolic scaling exponent are strongly negatively correlated [115], as predicted by the MLBH [16,26].…”
Section: Suggestions For Future Researchmentioning
confidence: 67%
“…As body size increases, surface-area-to-volume ratios decline, making it relatively harder for large endotherms to shed heat [6]. But by virtue of their larger body mass reserves and slower metabolic rate [20], it might be that large animals can go for a longer time without feeding than smaller species can, and thus have greater behavioural plasticity to 'sit out' hot spells. Additional research on body mass and other key ecological traits could improve the accuracy of predictions about species responses to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…We then ask whether relative temperature sensitivity varies with body size. It is thought that much of the variation among species in susceptibility to climate change could be trait-based [17,18]; body size, in particular, is a fundamental ecological trait that affects numerous facets of an organism's ecology [19,20]. But the effects of body size on mammal responses to warming are mixed [6,20,21], suggesting that size-based vulnerability of animals to climate change remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%